Glass fibre reinforced polymer in Malaysian construction industry - Mohd. Sam, Abd. Rahman (2007)
Nowadays, strength and durability are important criteria that need to be taken into consideration in the design and selection of materials to ensure the structure able to provide the service as designed. Many reports highlighted that quite a number of reinforced concrete structures throughout the world are suffering from durability problem such as corrosion. The reports highlighted the seriousness of the problem of deteriorated infrastructure all over the world such as in Canada, the USA and Europe (Khabari and Zhao 2000).